Weak Convergence of an Iterative Scheme with a Weaker Coefficient Condition - Kimura, Yasunori (Modeling, Computation And Optimization, 2009)
We deal with a generalized proximal point algorithm for a sequence of m-accretive operators in Banach spaces. We investigate the condition of coefficients more deeply, and obtain weak convergence of an iterative scheme with a weaker coefficient condition.